PENGARUH UMUR BIBIT DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (ALLIUM ASCALONICUM L) SISTEM TSS (TRUE SHALLOT SEED) - Harokat, Andy; Surawinata, E. Tadjudin; Sungkawa, Iman (Agroswagati : Jurnal Agronomi, 2021)
The aims of this research was to determine the effect of the interaction and the best results from the treatment of seedling age in the nursery and plant spacing of shallot (Allium ascalonicum L.). This research was conducted at the Practical Garden of SMK Negeri 5 Kuningan in Ciawilor Village, Ciawigebang District, Kuningan Regency, which is located at an altitude of ± 250 meters above sea level, the air temperature ranges from 25oC - 29oC. This study was arranged using Factorial RAK, with two factors, namely the age of plant seeds (7 MSS, 6 MSS, 5 MSS, and 4 MSS) and plant spacing (10 x 10 cm, 15 x 10 cm, 15 x 15 cm, 15 x 20 cm, and 20 x 20 cm). The results showed an interaction occurred at the average plant height of 42 DAP and independent influence on the average plant height at 21, 28 and 35 DAP, the average number of leaves per clump at 21, 28, 35 and 42 DAP, the average the number of tillers per clump at 35 and 42 DAP, and LPT at 21-28, 28-35 and 35-42 DAP. The weight of dry bulbs per plot showed the best shallot yields were in the treatment of seedling age B4 (4 MSS) with a yield of 3,04 kg/plot with a productivity value of 6,95 tons/ha and treatment with a spacing of J1 (10 x 10 cm) with yields 5,07 kg/plot is equivalent to 11,59 tons/ha.